Perception of municipal health secretaries of the management of work and education in the public network of the Brazilian Unified Health System (SUS) - Vermelho, Sônia Cristina; Figueiredo, Gustavo (Saúde e Sociedade, 2017)
The article presents empirical research results with municipal health secretaries of a micro-region of Paraná. We aim to analyze the mechanisms of work and health education management during the implementation of basic care networks in the region. We used an integrated qualitative-quantitative method, with a questionnaire and semi-structured interviews with 24 managers. The material was transcribed, categorized and analyzed using the thematic content analysis method. The results indicated a reduced conception of work and education management, understood as processes independent from each other, limited to the offer of courses, without an understanding of the possibilities of an integrated management. There is a prevailing view of public sector management based on managerialism and on performativity, which are considered neoliberal political technologies. Our results allow us to affirm that in the perception of the municipal health secretaries, the main difficulties for the implementation of educational actions are: the time-space logistics to articulate work and training, the workers’ lack of interest, and political and legal external determinants. Among the incentives for the training of professionals, the financial issue stands out, which at times of economic crisis is worrying, as it may reveal a paralysis in these professional training practices. It is also necessary to consider the existence of a huge gap between the theoretical debate in the health education field and the discrepant reality found in these municipalities. Finally, we concluded that although there is a consensus on the importance of health education for the quality of care and for the organization of the work process in health services, there is still a long way to improve the management of these actions in the Brazilian Unified Health System.